Status Differences and Knowledge Transfer: The Effect of Incentives - Haesebrouck, Katlijn; Cools, Martine; Van den Abbeele, Alexandra (The Accounting Review, 2018)
ABSTRACT We examine how incentive systems influence knowledge transfer between group members with equal or different status who solve an interdependent task. In our experiment, group members receive group or individual incentives, while status is manipulated by assigning job titles with corresponding role descriptions. Although all conditions require knowledge sharing to maximize payoffs, our results suggest that significantly more knowledge is shared under group incentives relative to individual incentives when status differences are present, whereas the amount of knowledge shared does not differ across these incentive manipulations for equal-status groups. These findings are in line with theory suggesting that individual incentives can motivate knowledge sharing among equal-status groups, but cannot overcome the negative interactions that arise under status differences. Instead, group incentives are required to induce cooperative behavior that mitigates the negative effects of status differences on knowledge sharing. We contribute to the literature and practice by showing that the effect of incentives depends on the social context and that job titles can have unintended consequences.